Introduction—Ensuring access to affordable, reliable, sustainable and modern energy in the MENA region: Legal, institutional and policy developments - Imad Antoine Ibrahim (14158998) (2023)
‘Energy transition’ is a new buzzword that emerged in recent years to describe the efforts conducted at the global, regional and national levels to shift from the use of conventional resources that have caused major environmental problems towards cleaner versions. Projects, funding and much more have been established to facilitate the transition worldwide, where some nations took this responsibility more seriously than others. Energy transition is not only a shift towards clean energy but also covers its storage, infrastructure and distribution. It is also expected to impact the global economy. The main factors allowing such transition are public pressure, the reduction in the costs of renewables, as well technological developments. It is an extremely complicated process that includes management and governance in a context of great uncertainty and ambiguity. While factors such as collaboration and public funding may help facilitate the shift, others such as public opposition to it can cause further complications, as society’s support is needed to make the structural changes through measures unique to each country, considering their priorities. Other Information Published in: The Journal of World Energy Law & Business License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jwelb/jwad004